Analysis of the determinants of farmer participation in sorghum farming among small-scale farmers in Siaya County, Kenya - Okeyo, Samuel O.; Ndirangu, Samuel N.; Isaboke, Hezron N.; Njeru, Lucy K.; Omenda, Jane A. (Elsevier, 2020)
Sorghum as a drought tolerant crop provides an alternative opportunity towards increasing food production in the face of global climate change, mostly affecting Sub-Saharan Africa. Kenya is in the fore front in increasing the production of sorghum since its landmass is 80 percent arid and semi-arid. Few studies have evaluated farm and farmer related characteristics affecting adoption of sorghum production. Therefore, the objective of this study was to determine how selected factors affect the propensity of farmers to adopt sorghum production in Siaya County, Kenya. A total of 300 households were randomly selected as respondents in four sub-counties under sorghum production. Data was collected using semi-structured interview schedules administered to the selected farm households. The selected factors were subjected to descriptive analysis, while binary logistic regression model was applied for the quantitative analysis of the effect of these factors on adoption of sorghum production. The results of the regression analysis reveal that farm size, land size allocated to maize, beans and groundnut enterprise, land ownership and access to training significantly affected adoption of sorghum farming. The study underscores the significant impact of resource allocation decisions on uptake of sorghum production among farm households. Our findings show that farmers with larger farms are more likely to adopt sorghum production. However, due to industrial demand and food security potential of sorghum, we recommend that the extension service providers should also incentivize those with smaller farms to participate in sorghum production. Policies that will make sorghum enterprise more competitive over other crops, both at the farm and market level, are key. In addition, agricultural development policies should target provision of such services like training to streamline sorghum production in the arid and semi-arid areas in Kenya.
Keywords: Arid and semi-arid; Binary logistic; Production resource; Sorghum adoption